2019
DOI: 10.1080/12298093.2019.1623979
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Enzymatic Activity of Halotolerant and Halophilic Fungi from the Great Sebkha of Oran in Northwestern of Algeria

Abstract: The Great Sebkha of Oran is a closed depression located in northwestern of Algeria. Despite the ranking of this sebkha among the wetlands of global importance by Ramsar Convention in 2002, no studies on the fungal community in this area have been carried out. In our study, samples were collected from two different regions. The first region is characterized by halophilic vegetation and cereal crops and the second by a total absence of vegetation. The isolated strains were identified morphologically then by mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 71 publications
3
40
1
1
Order By: Relevance
“…Some studies have explored the influence of salt in the enzymatic activity of marine fungi. For example, Chamekh et al [69] evaluated different enzymatic activities of halotolerant and halophilic fungi and Arfi et al [70] reported the presence of more than 400 lignocellulolytic enzymes from the mangrove fungus Pestalotiopsis sp. The authors concluded that the presence of salt modifies lignocellulolytic enzyme composition, with an increase in the secretion of xylanases and cellulases and a decrease in the production of oxidases, as we also observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have explored the influence of salt in the enzymatic activity of marine fungi. For example, Chamekh et al [69] evaluated different enzymatic activities of halotolerant and halophilic fungi and Arfi et al [70] reported the presence of more than 400 lignocellulolytic enzymes from the mangrove fungus Pestalotiopsis sp. The authors concluded that the presence of salt modifies lignocellulolytic enzyme composition, with an increase in the secretion of xylanases and cellulases and a decrease in the production of oxidases, as we also observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…3: no. 261 Patouillard (1903), ), Guechi & Girre (1994, Schubert et al (2003), Chliyeh et al (2014, Kedad & Bouznad (2018) Patouillard (1903), Kedad & Bouznad (2018). Maire (1933), Kedad & Bouznad (2018).…”
Section: Phaeosphaeriaceaementioning
confidence: 99%
“…1(livr. 9) Kachour (2004), Bouharati et al (2008), Harzallah et al (2009), Benzeghmane (2011), Belhoucine et al (2011), Ladjal (2012, Bessadat et al (2014), Kahoul et al (2014), Bensaci et al (2015), Bessadat et al (2017), Rebbouh (2016), Kedad & Bouznad (2018), Chamekh et al (2019) Jain, Curr. Sci.…”
Section: Phaeosphaeriaceaementioning
confidence: 99%
“…The mycobiota of hypersaline environments is dominated by members of Aspergillus, Penicillium, and other genera, such as Alternaria, Cladosporium, Fusarium, Debaryomyces, Scopulariopsis, Chaetomium, Wallemia, and Hortaea, which are well represented in ecological and biodiversity studies [96,97]. The species Gymnoascus halophilus, Aspergillus penicillioides, Hortaea werneckii, Phaeotheca triangularis, Aureobasidium pullulans, Trimmatostroma salinum, and some species of the genus Wallemia, like W. ichthyophaga, are recognized as obligately halophilic, or require high levels of salt above that of seawater [98,99]. However, antimicrobial compounds have not been reported from these species.…”
Section: Fungimentioning
confidence: 99%